Comparative Analysis of Intralesional Immunotherapy and Conventional Treatments for Non-Genital Warts: A Systematic Review and Network Meta-Analysis - Amr Molla; Muhammad Tobaiqi; Hossein Elbadawy; Raed Jannadi; Heba Eltahir; Emad Albadawi; Naweed Alzaman; Mohammed Aloufi; Mekky Abouzied; Muayad Albadrani (Mattioli1885, 2024)
Introduction: Warts, benign skin growths caused by various human papillomavirus strains, are categorized as genital and non-genital. Non-genital warts often lack noticeable symptoms but can lead to psychological distress due to factors like embarrassment. Traditional treatments, including physical and chemical methods, show limitations, prompting the exploration of novel approaches like intralesional immunotherapy. The clinical challenge lies in selecting the most effective modality. Objective: In our study, we used the network meta-analysis (NMA) as a statistical tool to explore the most effective intralesional immunotherapy interventions. Methods: Comprehensive searches of Web of Science, PubMed, Cochrane, and Scopus databases were conducted until December 2023. Eligible studies were analyzed for outcomes presented as risk ratios (RRs) with 95% confidence intervals (CI). Treatments were ranked using the P-score in an NMA performed with R software. Results: We included 68 RCTs in our study. For complete response, needling showed a significant difference compared to Candida albicans antigen (RR= 0.13, 95% CI [0.02; 0.99]) and Mw (RR= 0.12, 95% CI [0.02; 0.94]). In overall response, both bleomycin and furosemide with digoxin were significant compared to autoimplantation (RR= 0.46, 95% CI [0.24; 0.88]) and (RR= 0.40, 95% CI [0.18; 0.91]) respectively. Similarly, both were significant compared to cryotherapy (RR= 0.45, 95% CI [0.27; 0.76]) and (RR= 0.40, 95% CI [0.19; 0.82]) respectively. Conclusion: This NMA indicates needling, furosemide with digoxin, and PBP antigen stimulants as effective for non-genital warts, surpassing traditional treatments in complete and overall response. Direct comparisons in future research are warranted to confirm their superiority.